2010
DOI: 10.3846/jeelm.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Changes in Flowering Phases and Airborne Pollen Dispersion of the Genus Betula (Birch)

Abstract: The scientists evaluate the climate change by various methods. The long‐term phonological observation is a quite significant indicator of this phenomenon. Moreover, the forecasting of plants flowering period or changing of amount of pollen production is important for guarantying of social health. The aim of the research ‐ to analyze the interdependence of flowering changes and pollen concentration under the climate change according to the long‐term phenological data and evaluation of aeropalynological situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Taking into consideration the fact that air temperature determines the processes of pollen release from plants (Veriankaitė et al 2010a) and the spread of particles may be determined by other meteorological parameters, the significance of air humidity for modeled processes was evaluated. The research results revealed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration the fact that air temperature determines the processes of pollen release from plants (Veriankaitė et al 2010a) and the spread of particles may be determined by other meteorological parameters, the significance of air humidity for modeled processes was evaluated. The research results revealed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Lithuania, the spatial variation of the start of flowering was considerable, differences could reach 24 days, and the values of the variation coefficients did not exceed 9%. Generally, Betula pendula started to flower at the beginning of May, with a tendency to significantly accelerate [14,25]. If birch flowering came earlier, the difference between the earliest and the latest flowering of plants in Lithuania increased.…”
Section: Discussionmentioning
confidence: 99%
“…In Lithuania in the 70s, Betula species started to flower mainly in May, and in the 90s in late April and the average advance was 10-15 days. At the beginning of the twenty-first century (2004)(2005)(2006)(2007)(2008) birches flowered even in the middle of April [14,25]. The authors showed warming as a cause of this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Menzel et al (2006) reported an advance of flowering around 2.5 days per decade from 1970 to 2000. The correlation between earlier pollen dispersal and increasing spring temperature has been widely demonstrated, e.g., in species belonging to the order Fagales in temperate climates (Bortenschlager and Bortenschlager 2005), and in Betula (Emberlin et al 2002;Frei and Gassner 2008;Yli-Panula et al 2009;Veriankaitė et al 2010 and references therein), Alnus (Emberlin et al 2007;Gonzáles-Parrado et al 2006;Rodríguez-Rajo et al 2006), and Castanea (Rodríguez-Rajo et al 2005. A similar advance with increasing winter/spring temperature has been observed also in Platanus (Norris-Hill 1998; Sabariego Ruiz et al 2008).…”
Section: Introductionmentioning
confidence: 95%